Synthesis, Characterization and Antibacterial Properties of Silver Nanoparticles in Clay and Organic Polymers as Nanocomposites - Shameli, Kamyar (2011)
In this study, silver nanoparticles (Ag NPs) with the small size (2.12–30.63 nm) were successfully synthesized in the lamellar space of montmorillonite (MMT), montmorillonite/chitosan (MMT/Cts), porous zeolite framework and external surface layer of talc by chemical reducing agent in the absence of heat treatment. The most favourable experimental condition for the synthesis of Ag NPs in the MMT, talc, zeolite nanocomposites (NCs) and silver/montmorillonite/chitosan bionanocomposites (Ag/MMT/Cts BNCs) are described in terms of the initial concentrations of AgNO3. The mean diameters and standard deviation of Ag NPs in all of solid supports increased gradually with the increase of silver ions concentration. The external morphologies indicate that there are no noteworthy morphological distinctions between solid substrates and Ag NPs incorporated to them. The Ag NPs by the physical synthetic route were synthesized in the lamellar space of MMT/Cts utilising the UV-irradiation reduction method in the absence of reducing agent or heat treatment. The properties of Ag/MMT/Cts BNCs were studied as the function of UV-irradiation times. UV-irradiation disintegrated the Ag NPs into smaller size until a relatively stable size and size distribution were achieved. The silver nanocrystals were also synthesized by another physical method into the interlamellar space of MMT by using ƴ-irradiation in the absence of reducing agent or heat treatment. The properties of Ag/MMT NCs and the diameters of Ag NPs were studied as a function of ƴ-irradiation doses. The results from the UV-visible spectroscopy and TEM demonstrated that increasing the ƴ-irradiation doses enhanced the concentration of Ag NPs. In addition, the particle size of Ag NPs gradually increased from 1 until 20 kGy. When the ƴ-irradiation doses increased from 20 to 40 kGy, the particle diameters decreased suddenly as a result of the induced fragmentation for Ag NPs. Moreover silver/poly(lactic acid) nanocomposites (Ag/PLA NCs) films were investigated, while Ag NPs were synthesized into the biodegradable PLA as a polymeric matrix and stabilizer in the presence of sodium borohydride as a chemical reduction agent in diphase solvent. In all preparation, MMT, talc and zeolite were used as the inorganic solid supports and poly(lactic acid) was used as organic polymeric matrix. The silver nitrate, chitosan, and sodium borohydride were used as the silver precursor, natural and biodegradable polymeric stabilizer, and the reduction agent respectively. The crystalline structure of Ag NPs for all of samples, average size and size distributions, surface plasmon resonance, surface morphology, and functional groups were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), UV-visible spectroscopy (UVvis), scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) respectively. The XRD analysis confirmed that the crystallographic planes of the silver crystals were the face-centred cubic (fcc) types. The UV-visible absorption spectra showed the peaks characteristic of the surface plasmon resonance (SPR) bonds of Ag NPs. The antibacterial activities of Ag NPs were investigated against Gram-negative and Gram-positive bacteria by the disk diffusion method using Mueller-Hinton Agar (MHA) at different sizes and amounts of Ag NPs. Results show that the antibacterial activity of Ag NPs can be modified with the particle size of Ag NPs.